[Molecular identification of Aspergillus fumigatus isolated from patients with invasive aspergillosis] - Béjar, V (2019)
The objective of the study was to identify molecularly-isolated strains of Aspergillus from patients with invasive aspergillosis (IA); these strains were primarily typed as Aspergillus fumigatus sensu lato by conventional phenotypic methods. We worked with 20 strains from the mycology section of the Institute of Tropical Medicine "Daniel A. Carrión." To obtain the fungal DNA, thermal shock, enzymatic treatment, and silica gel column techniques were used; and it was stored at -20°C to preserve it. The real-time polymerase chain reaction (qPCR) procedure included fluorochrome-labeled primers, which amplified the specific sequences of A. fumigatus. Fluorescence was measured with the thermocycler at the end of the hybridization phase of each cycle. It was molecularly-identified that only 50% of the strains studied belong to the species Aspergillus fumigatus sensu stricto.